LAW OF ATTRACTION DALAM PERSPEKTIF ISLAM - Nurfaiza, Najma Ranni; Jaenuri, Jaenuri (Muta'allim: Jurnal Pendidikan Agama Islam, 2024)
Recently there is a law that is quite famous in modern society, the law of attraction. It is believed that everything that humans think about will happen in the future. In Islam it turns out that humans already know the law of attraction in everyday life because we always pray as Allah SWT commands. This study uses the narrative review method to identify, evaluate, and synthesize research results and ideas. Humans were created as intelligent beings by God. Humans think, in the way of thinking humans are divided into two, namely the conscious and subconscious. Every realm of mind has a function. The conscious has a function of logic and the subconscious has a function of creativity. Rhonda Byrne, author of The Secret, then explains that the law of attraction is felt by everyone as well as the law of gravity. Humans submit to nature, without realizing that nature is God's creation. So when humans are subject to the laws of nature, humans are also servants of nature. The law of attraction teaches us to imagine what we want, this is in line with Islam that Allah SWT loves His servants who always pray to Him. In essence, it is only to Allah that Muslims beg and ask for everything because Allah is the Greatest.